2022
DOI: 10.3389/fdgth.2022.838538
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Study of the Reasons and Time Involved for Dental Providers' Medical Consults

Abstract: BackgroundPatient-reported medical histories and medical consults are primary approaches to obtaining patients' medical histories in dental settings. While patient-reported medical histories are reported to have inconsistencies, sparse information exists regarding the completeness of medical providers' responses to dental providers' medical consults. This study examined records from a predoctoral dental student clinic to determine the reasons for medical consults; the medical information requested, the complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…59 Among the most common reasons for dental providers to seek medical consults, almost 40% are related to medication information and 1 out of every 4 requests concern medication lists. 60 However, this is ineffective given that numerous attempts are typically required to contact medical providers, the information is often incomplete, and the process is markedly delayed in 25% of cases. 60 It has been suggested that the intervention of pharmacists in the medication conciliation process might help to improve the accuracy of the medication lists available to dentists.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…59 Among the most common reasons for dental providers to seek medical consults, almost 40% are related to medication information and 1 out of every 4 requests concern medication lists. 60 However, this is ineffective given that numerous attempts are typically required to contact medical providers, the information is often incomplete, and the process is markedly delayed in 25% of cases. 60 It has been suggested that the intervention of pharmacists in the medication conciliation process might help to improve the accuracy of the medication lists available to dentists.…”
Section: Discussionmentioning
confidence: 99%
“…60 However, this is ineffective given that numerous attempts are typically required to contact medical providers, the information is often incomplete, and the process is markedly delayed in 25% of cases. 60 It has been suggested that the intervention of pharmacists in the medication conciliation process might help to improve the accuracy of the medication lists available to dentists. 16 It has also been proposed that, to avoid discrepancies between DMR and MMR, information concerning medications should be shared between medical and dental health record data, 61 or better still, the medical and dental information for each patient should be included in a single unified electronic health record.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several papers—in addition to those included in this review—have advocated for the use of computer-aided diagnosis (CAD) as a means of providing an interface for managing and simplifying complex variables involved in the traditional clinical diagnosis process [ 19 , 21 , 69 , 74 , 85 ]. The use of computer programs in dentistry has been rapidly evolving for quite some time now with the advent and popularisation of digital workflow systems providing a way to improve communication—both between practitioners and with patients—as well as a means of improving overall efficiency and decreasing laboratory workload [ 70 , 71 , 86 , 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the existing AECG criteria [ 21 , 22 ] incorporate only the complete manifestation of the disease, and since they are not particularly relevant to detect SD in clinical practice, it is necessary to characterize these patients’ clinical characteristics using EHR data for research studies. The digitization of dental care data and the establishment of regional and state-wide health information exchanges (HIE), with increased interoperability between EHRs, offer the opportunity to link EDR and EHR data to identify a larger cohort of SD patients and study their oral health [ 36 , 37 ]. Therefore, in this study, we matched and linked the Indiana University School of Dentistry’s (IUSD) patients’ EDR data with their EHR data available through the state-wide Indiana Health Information Exchange (IHIE).…”
Section: Introductionmentioning
confidence: 99%